Topical Issues of the Theory and Practice of the Prosecutor’s Refusal to Accuse at the Stage of Preparing a Criminal Case for Trial - N. V. Spesivov (Сибирское юридическое обозрение, 2019)
The article is devoted to the consideration of the problem of the legality of the prosecutor’s refusal to accuse them at the stage of preparing a criminal case for trial. From the point of view of theory and practice, the Author analyzes the possibility and expediency of the prosecutor’s refusal to accuse at the preliminary hearing, as well as some procedural issues arising at this stage when the criminal case is returned to the prosecutor to eliminate violations of the criminal procedure law. The Author comes to the conclusion that the prosecutor’s refusal to accuse at this stage is not only possible, but also fully meets the objectives of his activities as a guarantor of ensuring the rights and freedoms of citizens involved in the criminal justice sphere, as well as setting the criminal process as the basic principle. Nevertheless, there are still legislative and law-enforcement problems associated with the participation of the prosecutor in the preliminary hearing, which require reflection and resolution.